Histology of Pericardial Tissue Substitutes Used in Congenital Heart Surgery. (September 2016) - Majeed, Amara; Baird, Christopher; Borisuk, Michele J.; Sanders, Stephen P.; Padera, Robert F.
Pericardium is used as a tissue substitute during pediatric heart surgery. However, little is known about the histological characteristics of pericardial tissue substitutes. We searched our clinical and Pathology databases to identify cases in which glutaraldehyde-preserved autologous pericardium, PhotoFix bovine pericardium, or Peri-Guard Repair Patch glutaraldehyde-preserved bovine pericardium was used as patch material during cardiac surgery and in which explanted tissue substitute was available for histologic examination. Tissue sections were stained with hematoxylin and eosin, Masson trichrome, and Movat pentachrome, and were graded for inflammation, tissue substitute degeneration, neointima formation, and calcification. Nonparametric statistical methods were used to test differences between groups because of small sample size. The eight patients who received PhotoFix pericardium were older (median 10 months vs 10 days, P < 0.05) and the material was in situ longer (median 14 vs 2.5 months, P < 0.05) compared to the eight who received autologous pericardium. Only three patients received glutaraldehyde-preserved bovine pericardium precluding statistical comparison. Inflammation and tissue degeneration were greater in PhotoFix pericardium compared to autologous pericardium but were no more than moderate. Neointima formation and calcification did not differ significantly between the two groups. PhotoFix bovine pericardium is associated with more inflammation and material degeneration but calcification, and neointima formation are similar to autologous pericardium. Although the short-term outcomes are acceptable, calcification and degeneration seen in some cases suggest that long-term outcomes and performance at certain anatomic locations need further study.